STUDY ON WATERFLOODING IMPLEMENTATION TO ENHANCE OIL RECOVERY FROM RESERVOIR Q-3 IN THE X FIELD - DICKY DUSYANTO (NIM : 22208013), ERWIN
Reservoir Q-3 in the X-Field is part of Kutai Basin in East Kalimantan. In this study Q-3 zone is selected to be developed further, as a justification for waterflood implementation in the X-Field. This zone is preferable as a waterflood candidate since the Primary Recovery Factor is relatively low. Basically, the Q-3 zone is divided into three main blocks, W,E, and M. Primary recovery factor is estimated as 4.74% (31 March 2010). This low figure has been the consideration of the need for efforts to increase the oil recovery using enhanced oil recovery. This study emphasizes on reservoir simulation study which consists of initialization, history matching, and forecast using various scenarios. Initialization result for Q-3 zone is 14.7 MMSTB which has 4.5 % difference as compared to volumetric calculation. This difference is caused by lenses reservoir distribution with various water oil contacts, while on the other hand the well data for each block is very limited. The development scenarios in this study are as follows: - Scenario I (Existing/Base Case) Cumulative production is predicted to be 936.876 MSTB, with 6.37% Recovery Factor. - Scenario II. (Existing + well reactivation). Cumulative production is predicted to be 1305.87MSTB with 8.88% Recovery Factor. - Scenario III. (3 producers + 4 injectors). Cumulative production is predicted to be 1396.89 MSTB with 9.50% Recovery Factor. - Scenario IV (4 producers + 7 injectors). Cumulative production is predicted to be 1453.14 MSTB with 9.88% Recovery Factor. - Scenario V (6 producers + 11 injectors). Cumulative production is predicted to be 2473.5 MSTB with 16.82% Recovery Factor. - Scenario VI (7 producers + 13 injectors). Cumulative production is predicted to reach 2740.26 MSTB with 18.89% Recovery Factor